Artificial Intelligence in Clinical Pharmacy: From Decision Support to Prescription Execution. - Jiang, Wenshuo; Wang, Yuntian; Shi, Weizhong; Li, Cao; Li, Mingda; Tang, Yongqiang; Yue, Xiaolin; Zhao, Zhigang; Bardhan, Munmun (Journal of Clinical Pharmacy & Therapeutics, 2026)
Artificial intelligence (AI) is emerging and showing great potential in optimizing clinical pharmacy. This review aims to provide an overview of applications and advances of AI in clinical pharmacy. The findings illustrated that AI can assist in various stages from decision support to prescription execution supporting safer and more effective therapeutic practice. Machine learning and natural language processing are useful tools for tasks such as drug therapy recommendation, precision dosing, adverse drug event prediction and improving medication adherence. This study summarizes the latest progress in AI technologies within clinical medication from the view of both pharmacists and AI specialists. Future efforts should focus on addressing challenges like data quality issues to steadily advance AI‐driven clinical medication development.